Materiality Analysis in Sustainability Reporting: A Method for Making it Work in Practice - Calabrese, Armando; Costa, Roberta; Levialdi Ghiron, Nathan; Menichini, Tamara (European Journal of Sustainable Development, 2017)
Sustainability reporting is the practice of measuring, disclosing, and being accountable to internal and external stakeholders for the company’s ability to achieve sustainable development goals (SDGs) and manage impacts on society. According to the Global Reporting Initiative (GRI) G4 guidelines, the purpose of materiality analysis in sustainability reporting is to determine those economic, environmental and social issues that are the most significant to company and its stakeholders. A key challenge is to ensure completeness in covering all the aspects that are material from internal analysis, business strategy and stakeholder perspective. Thus, the views of different stakeholders need to be taken into account dealing with subjectivity of judgments. Current sustainability literature offers few studies aimed to support companies in materiality analysis through quantitative and practical approaches. Based on a critical review of these studies, the present paper provides suggestions for the development of a new and more effective method. Keywords: Sustainability reporting, materiality analysis, stakeholder engagement, Global Reporting Initiative (GRI), decision support methods.